IMPLEMENTASI PEMROGRAMAN WEB UNTUK MENINGKATKAN EFISIENSI LAYANAN INFORMASI - Alivia Risma Dewi Safana; Dendy Kurniawan (Jurnal Riset Teknik Komputer, 2025)
This study aims to examine the role of web programming in improving the efficiency of information services using a Systematic Literature Review (SLR) approach. Data were collected by systematically searching scholarly articles from reputable databases using predefined inclusion and exclusion criteria. The analysis was conducted qualitatively by categorizing findings based on application sectors, including education, health, public administration, and services. The results indicate that the implementation of web programming significantly accelerates service processes, improves data accuracy, and expands access to real-time information. Furthermore, the use of modern technologies such as responsive frameworks, model-driven approaches, and artificial intelligence integration enhances both efficiency and service quality. These findings emphasize that web programming is a crucial component of sustainable digital transformation strategies.